Resilient and Self-Healing Hyaluronic Acid/Chitosan Hydrogel With Ion Conductivity, Low Water Loss, and Freeze-Tolerance for Flexible and Wearable Strain Sensor - Hu, Yunping; Liu, Nannan; Chen, Kai; Liu, Mingxiang; Wang, Feng; Liu, Pei; Zhang, Yiyuan; Zhang, Tao; Xiao, Xiufeng (Frontiers in Bioengineering and Biotechnology, 2022)
Conductive hydrogel is a vital candidate for the fabrication of flexible and wearable electric sensor, due to their good designability and biocompatibility. These well-designed conductive hydrogels based flexible strain sensors show great potential in human motion monitoring, artificial skin, brain computer interface (BCI), and so on. However, the easy drying and freezing of conductive hydrogels with high water content greatly limited their further application. Herein, we proposed a natural polymer based conductive hydrogel with excellent mechanical property, low water loss, and freeze-tolerance. The main hydrogel networked was formed by the Schiff based reaction between the hydrazide grafted Hyaluronic acid and the oxidized chitosan and the added KCl worked as the conductive filler. The reversible crosslinking in the prepared hydrogel greened its resilience and the self-healing feature. At the same time, the synthetic effect of KCl and glycerol endowed our hydrogel with outstanding anti-freezing property, while glycerol also gave this hydrogel with anti-drying property. When this hydrogel was assembled as a flexible strain sensor, it showed good sensitivity (GF=2.64), durability, and stability even under cold condition (-37°C).